CARING DALAM ASUHAN KEPERAWATAN (Studi Eksploratory Berdasarkan Budaya Pasien) - PRIAMBODO, GALIH (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2015)
Caring is the central focus or core of nursing (Watson, 2009). Level of caring as anevaluation of health services in this era. Caring is an emerging concept of self or individual personality, because as another concept that is formed on the basis of social interaction, according Kagitcibasi and Berry (1989) in Santrock (2008) The concept of having one'sbehavior is a cross-cultural variation is influenced by the culture in which he lives. The statement above is the background of researchers studied, caring nurses categories basedculture. Exploratory research design was used, the sample using purposive sampling with 7patients in hospitals PKU Muhammadiyah Bantul. Retrieval of data using in-depth interviewswith semi tersektruktur question. Discussions with experts, caring based culture. The results of the interview showed caring categories according to the patient are: Attitude, Basic human needs, Spiritual, Information, Motivation, Communication Skills, Relationship Mutual Trust, Expression. The results of discussions with experts according to the patient's nursing categorycaring influenced by eastern culture.The conclusion of this study states that nurses caringcategory in accordance with the eastern culture. The statement shows a nurse caringinfluenced by, where the nurses lived.Keywords: moisture, dressings, SEFT, physiological, phsycological